Educação matemática e sua influência nos currículos prescritos e praticados: um estudo comparativo entre Brasil e Paraguai - Dias, Marcelo de Oliveira (2012)
This PhD thesis aims to develop comparative studies of mathematics curricula, prescribed and given in Brazil and Paraguay, duly organized and implemented from the 90s. Accordingly, in the chapters that follow is intended to identify the influences of research findings in mathematics education in the official documents of these countries. There is also exposure to common and specific aspects of the curricula of mathematics organized in Brazil and Paraguay, with regard to compulsory education. Nor are proposed to identify similarities and differences between the two systems, as well as relevant information evidencing compliance or rejection of mathematics teachers to curriculum guidelines prescribed in the official documents and data relating to curricula that actually become effective in the classroom. In order to carry out the research we adopted the methodology of comparative education, which is an analytical tool for the study of education systems. The thesis presents some contributions to be reflected by our community of mathematics education and educational managers of public policies